SWOT Analysis in Business Risk Awareness in MSMEs - Wahyudi, Dedi; T, Taryana; Tawil, Muhamad Risal; Z, Zulkifli; Sipayung, Baren (PT.KARYA GEMAH RIPAH, 2024)
This study reviews the SWOT analysis of these businesses, analyses business risks that MSMEs in the F&B industry face, and develops methods to mitigate those risks. Representing MSMEs in the growing food and beverage sector, Delightful Bites offers classic Indonesian pastries and drinks with unique flavours and creative touches. But they also face a lot of challenges and risks in running their firm, such as scarce resources, fierce rivalry, shifting costs for necessities, and shifting consumer tastes. This research uses a qualitative, case study methodology and is conducted through semi-structured interviews with the owners and managers of Delightful Bites, direct observation at the establishment, and analysis of business documents such as financial statements, business plans, promotional materials, and internal records. The results indicate that Delightful Bites has several strengths, including innovative products, a prime location, the use of substitute raw materials, and the use of local raw resources. These MSMEs are vulnerable to a number of risks, though, such as dependency on a single supplier, limited manufacturing capacity, and dependence on other factors. Furthermore, the study indicates that Delightful Bites has the ability to execute risk mitigation tactics, such as broadening its geographic reach by opening new branches or outlets in key locations, partnering with external parties for large-scale production, and allocating funds for more effective production facilities and equipment. It is hoped that this research will provide insightful information about practical approaches that MSMEs in the food and beverage sector can use to reduce risks and obstacles to business.